Does the host tree exert any influence on the aromatic composition of the black truffle (Tuber melanosporum)?. (15th November 2016) - Culleré, Laura; Ferreira, Vicente; Marco, Pedro; Venturini, María E.; Blanco, Domingo
Abstract: This work examines whether the host tree influences the aroma of Tuber melanosporum truffles. Samples were gathered in the same place (Teruel, Spain) and on the same day from four host trees: hazel, Portuguese oak, kermes oak and holm oak. The truffles were subjected to sensory and chemical analysis. The sensory analysis comprised two stages. The first was based on a sorting task while the second consisted of a descriptive analysis of the samples selected from the first test. The chemical analysis examined the volatile compounds having the greatest influence on the aroma of Tuber melanosporum by means of headspace‐solid phase microextraction followed by analysis by gas chromatography mass spectrometry (HS‐SPME‐GC‐MS). The sensory tests demonstrated that truffles gathered from the Portuguese oak had a more intense aroma than the rest of the samples, and significantly more than the holm oak truffles. The same pattern occurred for the animal descriptor which was considerably more intense in Portuguese oak truffles and significantly higher than that of holm oak truffles. Chemically, these differences can be explained by the levels of isoamyl alcohol and 3‐ethyl‐5‐methylphenol which were significantly greater in the Portuguese oak than the holm oak samples. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This work demonstrates that the samples of T. melanosporum collected from Portuguese oak have a significantly more intense aroma than those gathered from holm oak, and that the determining aromatic descriptor in the sensory characterisation of the truffles from Portuguese oak appears to be 'animal'. In chemical terms, it shows the importance of compounds such as isoamyl alcohol and 3‐ethyl‐5‐methylphenol for explaining the sensory differences found.